Modelling the transmission of HIV and HCV among injecting drug users in Rawalpindi, a low HCV prevalence setting in Pakistan. (23rd March 2009) - Vickerman, P; Platt, L; Hawkes, S
Abstract : Background: In 2007, a survey in Rawalpindi found the prevalence of hepatitis C virus (HCV) in injecting drug users (IDUs) to be low (17%), despite widespread needle/syringe sharing. This analysis uses modelling to explore hypotheses for the low prevalence of HCV to project the future HIV/HCV epidemic and to estimate the impact of a generic intervention. Methods: An HIV/HCV transmission model was developed and parameterised using data from Rawalpindi. By incorporating different assumptions about the relative frequency/importance of needle/syringe sharing events among "strangers" and people they have shared with before, and undertaking extensive uncertainty analyses to fit the model for each scenario, the validity of different hypotheses for the low HCV prevalence was determined. Model fits were used to project the future HIV/HCV epidemic and the impact of reducing needle/syringe sharing among different IDU subgroups. Results: The model projections suggest that the low HCV prevalence in Rawalpindi is probably due to most HIV/HCV transmissions occurring in a small IDU subgroup that shares needles/syringes frequently with strangers, with most needle/syringe sharing incidents being low risk. Projections suggest that the prevalence of HIV in IDUs will increase to 5–12% by 2015, and the prevalence of HCV will increase if HIV increases HCV transmission. Moderate reductions in needle/syringe sharing (>40%) could reduce the number of HCV/HIV infections (∼45%) if all IDUs are reached, although less impact is achieved if high-risk IDUs are not reached. Conclusions: Despite many needle/syringe sharing events possibly being low risk in Rawalpindi, the model projects that the prevalence of HIV/HCV in IDUs is likely to increase. This highlights the importance of intervening in this low prevalence setting.